Building A Superior Team Through Human Resource Development For PT Pertamina Employees In North Sumatra Region - Darmilisani; Randa Akbar (Yayasan Multidimensi Kreatif, 2025)
This study aims to analyze the impact of human resource development (HRD) on the formation of high-performing teams among employees at PT Pertamina, North Sumatra Region (Sumbagut). The background of this research is based on the importance of HR quality in building productive, collaborative, and adaptive teams in a dynamic work environment. A quantitative approach was used in this study, with data collection techniques including questionnaires and documentation. The results show that HR development—which includes training, career development, and coaching—has a positive and significant effect on the formation of high-performing teams. These findings provide practical implications for companies in designing HR development strategies aligned with team performance enhancement goals.